2014
DOI: 10.1111/eth.12234
|View full text |Cite
|
Sign up to set email alerts
|

How to Spot a Stranger's Egg? A Mimicry‐Specific Discordancy Effect in the Recognition of Parasitic Eggs

Abstract: Egg discrimination by hosts is an antiparasitic defence to reject foreign eggs from the nest. Even when mimetic, the presence of brood parasitic egg(s) typically alters the overall similarity of all eggs in a clutch, producing a discordant clutch compared to more homogenous clutches of composed only of hosts' own eggs. In multiple parasitism, the more foreign eggs are laid in the nest, the more heterogeneous the overall clutch appears. Perceptual filters and recognition templates cannot explain the known patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 62 publications
2
25
3
Order By: Relevance
“…That the rejection of foreign eggs does not depend on the degree of contrast between eggs and the nest lining (this study) provides support for earlier findings in hosts of egg-mimetic brood parasites that egg rejection is driven mechanistically by differences between foreign and own eggs (Cassey et al, 2008;Stevens et al, 2013;Moskat et al, 2014b). In contrast, cowbird eggs in robin nests are exceptional to this pattern: Croston and Hauber (2014a) showed that while robins' responses to artificial egg colors are generally predicted by chromatic JNDs differentiating foreign versus host eggs, artificial cowbird ground color-mimetic (beige) eggs are rejected in 100% of trials, despite their relatively low avianperceivable chromatic difference from robin eggs (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…That the rejection of foreign eggs does not depend on the degree of contrast between eggs and the nest lining (this study) provides support for earlier findings in hosts of egg-mimetic brood parasites that egg rejection is driven mechanistically by differences between foreign and own eggs (Cassey et al, 2008;Stevens et al, 2013;Moskat et al, 2014b). In contrast, cowbird eggs in robin nests are exceptional to this pattern: Croston and Hauber (2014a) showed that while robins' responses to artificial egg colors are generally predicted by chromatic JNDs differentiating foreign versus host eggs, artificial cowbird ground color-mimetic (beige) eggs are rejected in 100% of trials, despite their relatively low avianperceivable chromatic difference from robin eggs (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…In our case, we found that egg rejection by warblers was as high as 78.3% when the warbler eggs were artificially painted with ten extra spots. Although the spots deliberately painted on the egg could not represent the natural spot pattern of the egg, this manipulation is commonly used to test the effect of egg patterns on egg rejection by warbler hosts (Hauber et al 2006;Moskát et al 2008Moskát et al , 2014. Therefore, our study clearly confirms that egg-spot patterns play an important role in egg rejection by the Oriental Reed Warbler, consequently leading to high selection pressure for the cuckoo to evolve a better matching egg-laying strategy.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have pointed out the significance of the effect of spot pattern on egg recognition by the hosts (Hauber et al 2006;Moskát et al 2008Moskát et al , 2014. Therefore, we also conducted egg recognition experiments to confirm the importance of spot matching in this cuckoowarbler system.…”
Section: Egg Recognition Experimentsmentioning
confidence: 72%
“…Previous research on this host has shown that perceived eggshell coloration is an important cue for warblers’ egg rejection (Moskát et al. ; Hauber et al. ), while in our study population age, host genotype, and ambient light do not affect host egg rejection (Honza et al.…”
Section: Introductioncontrasting
confidence: 42%